2004
DOI: 10.1249/01.mss.0000113486.60548.e9
|View full text |Cite
|
Sign up to set email alerts
|

Pedometer Measures of Free-Living Physical Activity: Comparison of 13 Models

Abstract: The KZ, YX200, NL, and YX701 appear to be suitable for most research purposes. Given the potential for pedometers in physical activity research, it is necessary that there be consistency across studies in the measurement of "steps per day."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
479
2
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 633 publications
(516 citation statements)
references
References 12 publications
13
479
2
12
Order By: Relevance
“…The SW-701 (which has the same step count mechanism as the SW-200) consistently gave values within 3% of actual steps taken during a self-paced walk, on an individual basis (Cronbach's a 0.99) [21]. Subsequently, the SW-200 pedometer was found to be 1 of the 4 models (among 13) that accurately measures steps taken during free-living physical activity [22]. Finally, the SW-200 pedometer was found to have similar accuracy in normal-weight, overweight and moderately obese individuals [36].…”
Section: Outcome Measuresmentioning
confidence: 88%
See 2 more Smart Citations
“…The SW-701 (which has the same step count mechanism as the SW-200) consistently gave values within 3% of actual steps taken during a self-paced walk, on an individual basis (Cronbach's a 0.99) [21]. Subsequently, the SW-200 pedometer was found to be 1 of the 4 models (among 13) that accurately measures steps taken during free-living physical activity [22]. Finally, the SW-200 pedometer was found to have similar accuracy in normal-weight, overweight and moderately obese individuals [36].…”
Section: Outcome Measuresmentioning
confidence: 88%
“…They are simple in use, affordable, the output (e.g. steps take, steps/day) is extremely user-friendly [23] and accurately detects steps taken, as an indication of volume of physical activity [20][21][22]. This pilot study showed that the use of the pedometer, in combination with exercise counseling and the stimulation of lifestyle physical activity, is a feasible addition to the present-day pulmonary rehabilitation.…”
Section: Practice Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, PA levels of accelerometer were significantly correlated with EE (r ¼ 0.808, Po0.001). 16 In addition, Schneider et al 29 have compared 13 models of pedometer in a free-living condition, and have suggested that this accelerometer and three others are suitable for applied PA research. Since the device is a small and light accelerometer that can memorize data every 2 min for 6 weeks and directly transfer the data to an Excel file, it is a useful tool to assess the TEE, PA levels and step rate in a population study.…”
Section: Physical Activity and Obesity M Yoshioka Et Almentioning
confidence: 99%
“…A pedometer may help to give a quantitative estimate in a free-living population, as well as to increase motivation to initiate and to maintain walking as a regular activity. 15,16 A program of cognitive-behavioral therapy (CBT) for obesity has been operative in our unit since 1992. 17 Based on the LEARN program for weight control, 18 it includes a few notions on physical activity, but the compliance of patients to exercise has never been systematically tested.…”
Section: Introductionmentioning
confidence: 99%